Effects of temperature on somatic growth, gastric pepsin activity, and endocrine dynamics in orangefin labeo (Labeo calbasu) - Masuda Sultana Mimi; Mazlan Abd Ghaffar; Md. Akhtar Hossain; Simon Kumar Das; Md. Nushur Islam; Mohammad Lutfar Rahman; Md. Abdul Kader; Sabuj Kanti Mazumder (Journal of Fisheries, 2026)
This study investigated the effects of varying water temperatures on somatic growth, digestive enzyme activity, and endocrine responses in orangefin labeo (Labeo calbasu), a commercially important freshwater fish species. The experiment was performed in triplicate using 100 L glass aquaria at four temperature levels: 22, 26, 30, and 34°C. Over a 60-day experimental period, growth performance, pepsin activity, and hormonal dynamics were analyzed to identify optimal thermal conditions for aquaculture. Results demonstrated that 30°C was the most favorable temperature, yielding the highest specific growth rate (SGR: 0.45±0.05% day–1, n = 10), weight gain (3.07±0.70 g, n = 10), and length increase (1.29±0.57 cm, n = 10). In comparison, 22°C exhibited the lowest growth metrics (one-way ANOVA: p < 0.05). A thermal threshold for enzymatic efficiency was shown by significantly lower pepsin activity at both lower (22°C) and higher (34°C) temperatures, whereas digestive pepsin activity peaked at 30°C (8.34±0.71 U37 mg protein–1). Endocrine analysis revealed that the hormonal dynamics also temperature dependent. Reproductive hormones-follicle-stimulating hormone (FSH: 1.45±0.10 mIU mL⁻¹), luteinizing hormone (LH: 1.61±0.04 mIU mL⁻¹), testosterone (1.50±0.01 ng dL⁻¹), and estradiol-17β (E2) reached peak at 30°C which were higher than in other treatments (p < 0.05). Overall L. calbasu exhibited optimal growth, digestive efficiency, and reproductive performance within a narrow temperature range of 26–30°C (p < 0.05). These findings underscore the species’ sensitivity to temperature variation and highlight the importance of maintaining stable thermal conditions to ensure sustainable productivity and conservation in aquaculture.